2006
DOI: 10.1051/0004-6361:20053740
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wavelength study of coronal waves associated with the CME-flare event of 3 November 2003

Abstract: The large flare/CME event that occurred close to the west solar limb on 3 November 2003 launched a large-amplitude large-scale coronal wave that was observed in Hα and Fe xii 195 Å spectral lines, as well as in the soft X-ray and radio wavelength ranges. The wave also excited a complex decimeter-to-hectometer type II radio burst, revealing the formation of coronal shock(s). The back-extrapolation of the motion of coronal wave signatures and the type II burst sources distinctly marks the impulsive phase of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
4
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 86 publications
(119 reference statements)
6
97
4
1
Order By: Relevance
“…This correlation could not be established for EIT wave speeds (Klassen et al, 2000), most likely due to the severe undersampling of the waves' kinematics. A kinematical consistency (in terms of distances/heights and speeds) between type II bursts and coronal waves was also found in a large number of case studies (e.g., Vršnak et al, 2006;Pohjolainen et al, 2008;Grechnev et al, 2011b,a;Kozarev et al, 2011;Ma et al, 2011;Kumar and Manoharan, 2013). An example is shown in the right panel of Figure 15.…”
Section: Metric Type II Radio Burstssupporting
confidence: 57%
See 3 more Smart Citations
“…This correlation could not be established for EIT wave speeds (Klassen et al, 2000), most likely due to the severe undersampling of the waves' kinematics. A kinematical consistency (in terms of distances/heights and speeds) between type II bursts and coronal waves was also found in a large number of case studies (e.g., Vršnak et al, 2006;Pohjolainen et al, 2008;Grechnev et al, 2011b,a;Kozarev et al, 2011;Ma et al, 2011;Kumar and Manoharan, 2013). An example is shown in the right panel of Figure 15.…”
Section: Metric Type II Radio Burstssupporting
confidence: 57%
“…Figure 14b illustrates the spatial association of the type II burst source with the Moreton wave in the event reported by Khan and Aurass (2002). In the limb event studied by Vršnak et al (2005Vršnak et al ( , 2006, a complex type II burst was found to propagate obliquely through the corona, but a broad-band radio source was connecting it with the Hα, EIT, and SXR wavefronts in the low corona (cf. Section 3.3.1).…”
Section: Metric Type II Radio Burstsmentioning
confidence: 95%
See 2 more Smart Citations
“…There have been many studies of the possible association of SRBT II with either flares or CMEs [153][154][155][156][157][158][159][160][161][162]. SRBT II has extensively studied to understand their sources and in connection with CMEs and Solar Energetic Particles (SEP) events [50,163] based on signatures of the shock-associated plasma oscillate signatures of type II bursts occurred near off after the maximum of chromosphere flare.…”
Section: Volume 35mentioning
confidence: 99%